ASSOCIATION OF ANXIETY AND DEPRESSION WITH TINNITUS IN YOUNG ADULTS - Shaid, Fazlina; Salman, Henna; Khattak, Madiha; Hamid, Naila (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the association of anxiety and depression in young adults with hearing loss and tinnitus. Methodology: A cross-sectional study was conducted in the outpatient department (OPD) of Otorhinolaryngology Head and Neck Surgery, Khyber Teaching Hospital (KTH), Peshawar, in young adults from April 2019 to September 2019. A total of 370 patients were enrolled with consecutive sampling. The study population was divided into two groups for comparison purposes. A hearing loss only group (HL group) and a hearing loss with tinnitus group (HLT group). Tinnitus handicap inventory (THI) was used to diagnose tinnitus. For anxiety and depression Hospital Anxiety and Depression Scale (HADS) was utilized to diagnose anxiety and depression. Data was analyzed by using SPSS version 22. Categorical variables were described as frequencies and percentages. Association of tinnitus with hearing loss and anxiety and depression was determined by using chi square test with p value <0.05 as statistically significant. Results: Among patients with tinnitus and hearing loss, 46.2% were in the age range of 20-29 years and 53.8 % were in 30-40 years range. Males were predominant with 63%. Out of 173 patients, 38.7 % had anxiety while 46.2% had depression. The association of anxiety and depression with tinnitus and hearing loss was statistically significant with a p value of â‰¤0.05. Conclusion: Tinnitus with hearing loss in young adults is on the rise these days. The results showed a strong association between anxiety, depression and hearing loss with tinnitus in young adults as compared with hearing loss only.